Про вплив на рівновагу в економічній системі нелінійної залежності структури споживання товарів від ціни - Makhort, А. P. (The National Technical University of Ukraine "Igor Sikorsky Kyiv Polytechnic Institute", 2013)
The equilibrium conditions of an open economy system, contained monopolies, are investigated. The principles of economy equilibrium are set in a Walras sense. The presence of a goods production in the model is considered. All consumers in the economy are insatiable. The prices dependence of a consumption bundle formation of economy subjects are taken into account. The algorithm of determination of economy equilibrium states is proposed. The influence of prices dependence of consumption structure on characteristics of equilibrium states is considered. The conditions of absence of monopoly negative influences on the economy are investigated. The optimal equilibrium state in a sense of a satisfaction of consumption needs is determined. The estimation expressions of monopoly taxation are obtained. The relation between selection of a taxation strategy and the realization of a particular equilibrium state is discovered.